2009
DOI: 10.1016/j.virol.2009.01.003
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-2B Tax oncoprotein is modified by ubiquitination and sumoylation and displays intracellular localization similar to its homologue HTLV-1 Tax

Abstract: HTLV-1 is more pathogenic than HTLV-2B. The difference is generally attributed to the properties of their individual transactivating Tax proteins. By using internal Flag-6His tagged Tax-1 and Tax-2B, which display transcriptional activities comparable to the untagged proteins and can be recognized by a single anti-Flag antibody, we demonstrate that Tax-2B is modified by ubiquitination and sumoylation. In addition, Tax2B is distributed in punctuate nuclear structures that include the RelA subunit of NF-kappaB, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 22 publications
1
40
0
Order By: Relevance
“…Consistent with previous studies, Tax localization was heterogeneous with staining in both the cytoplasm and nucleus in 293T cells (Fig. 3A) (48). However, upon siRNA-induced silencing of STAMBPL1, a strongly nuclear distribution of Tax in the Tax speckled structure (TSS) was readily apparent (Fig.…”
Section: Stambpl1 Is a Positive Regulator Of Tax-mediated Nf-b Signalsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies, Tax localization was heterogeneous with staining in both the cytoplasm and nucleus in 293T cells (Fig. 3A) (48). However, upon siRNA-induced silencing of STAMBPL1, a strongly nuclear distribution of Tax in the Tax speckled structure (TSS) was readily apparent (Fig.…”
Section: Stambpl1 Is a Positive Regulator Of Tax-mediated Nf-b Signalsupporting
confidence: 91%
“…Wade Harper and obtained from Addgene (plasmid 22559) (45). Flag-Tax1 was a gift from U. Bertazzoni (48). The following antibodies were used in this study: anti-STAMBPL1 (ab99172; Abcam), anti-p100/ p52 (Santa Cruz Biotechnology), anti-␤-actin (AC15; Abcam), anti-IB␣ (C-21; Santa Cruz Biotechnology), anti-phospho-IB␣ (14D4; Cell Signaling), and anti-TATA-binding protein (anti-TATA-BP) (MAB3658; Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…A previous report suggested that, as Tax1, Tax2 was both ubiquitinated and SUMOylated (27). However, in this report, analyses of Tax1 and Tax2 modifications were performed in cells overexpressing ubiquitin or SUMO proteins, which may lead to false-positive results (60).…”
mentioning
confidence: 86%
“…Tax1 forms nuclear speckles (16)(17)(18)(19)(20) and is detected in Golgi/centrosome-associated cytoplasmic domains (21)(22)(23)(24). Although it is also detectable in the nucleus, Tax2 is predominantly found in the cytoplasm of the cells (25)(26)(27)(28) (for a review, see reference 29). Both proteins possess a nuclear export sequence located between amino acids (aa) 188 and 202 (30,31).…”
mentioning
confidence: 99%
See 1 more Smart Citation